Membrane Region M(2C2) in Subunit KtrB of the K(+) Uptake System KtrAB from Vibrio alginolyticus Forms a Flexible Gate Controlling K(+) Flux: AN ELECTRON PARAMAGNETIC RESONANCE STUDY - Hänelt, Inga (American Society for Biochemistry and Molecular Biology, 2010)
Transmembrane stretch M(2C) from the bacterial K(+)-translocating protein KtrB is unusually long. In its middle part, termed M(2C2), it contains several small and polar amino acids. This region is flanked by the two α-helices M(2C1) and M(2C3) and may form a flexible gate at the cytoplasmic side of the membrane controlling K(+) translocation. In this study, we provide experimental evidence for this notion by using continuous wave and pulse EPR measurements of single and double spin-labeled cysteine variants of KtrB. Most of the spin-labeled residues in M(2C2) were shown to be immobile, pointing to a compact structure. However, the high polarity revealed for the microenvironment of residue positions 317, 318, and 327 indicated the existence of a water-accessible cavity. Upon the addition of K(+) ions, M(2C2) residue Thr-318R1 (R1 indicates the bound spin label) moved with respect to M(2B) residue Asp-222R1 and M(2C3) residue Val-331R1 but not with respect to M(2C1) residue Met-311R1. Based on distances determined between spin-labeled residues of double-labeled variants of KtrB in the presence and absence of K(+) ions, structural models of the open and closed conformations were developed.